Peran Marketing Communication Dalam Meningkatkan Jumlah Hunian Pada Hotel Aerotel Smile Makassar - Nurfaisah , Andi; Zelfia, Zelfia; Muttaqin Mustari, Andi (UNIVERSITAS MUSLIM INDONESIA, 2022)
The objectives of this study are: (1) To determine the role of Marketing Communication in increasing the number of occupancy at the Aerotel Smile Makassar hotel. (2) To find out the communication marketing promotion model in increasing the number of occupancy at the Aerotel Smile Makassar Hotel. This research uses a descriptive qualitative approach. This study intends to describe an overview of the role of communication marketing in the increasing number of residences at the Aerotel Smile Makassar Hotel. The selected informants include people selected on the basis of certain criteria. This research was conducted by collecting data through observation, interviews and documentation. This research was conducted for one month and was located on Jl. Muchtar Lutfi No.38 Makassar City. The results showed that the role of marketing communication carried out by The Aerotel Smile Makassar Hotel in increasing the number of dwellings is to image hotel services through social media such as Instagram, Facebook and Twitter. The promotional model used by marketing communication in increasing the number of occupancy of the Aerotel Smile Makassar Hotel is advertising ( advertising), sales promotion, and direct marketing. The promotion carried out by the Aerotel Smile Makassar Hotel is quite optimal to attract the attention of potential visitors to visit the hotel but there is a number of dwellings that sometimes increase and decrease in different months so it can be said that the role and model of promotion of hotel communication marketing has not been maximized in increasing the number of occupancy.